2021
DOI: 10.3390/ma14040762
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Phases and Microstructures in Al-8Si Alloys with Different Mg Content

Abstract: Mg-containing high-silicon aluminum alloy is a heat-treatable aluminum alloy that is now widely used in the aerospace and automotive industries because of its high specific strength, high wear resistance and corrosion resistance, low thermal expansion coefficient, and low cost. More attention has been paid to optimizing the microstructure to increase the performance of this type of aluminum alloy. In the present work, the solidification processes of Mg-free and Mg-containing (0.33–1.32%) Al-8Si alloys were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…For instance, the solubility of Mg in Al containing 10 at.% Si is about 0.45 at.% Mg at 525 • C [57,58]. In Figure 3, we see that this results in a significant amount of π-Al8Mg3FeSi6 phase [59] inside alloy Mg0.60. The resulting loss of Mg from the Al grains explains the peak hardness of Mg0.60 not being higher than that of Mg0.45.…”
Section: Solute Balancementioning
confidence: 90%
“…For instance, the solubility of Mg in Al containing 10 at.% Si is about 0.45 at.% Mg at 525 • C [57,58]. In Figure 3, we see that this results in a significant amount of π-Al8Mg3FeSi6 phase [59] inside alloy Mg0.60. The resulting loss of Mg from the Al grains explains the peak hardness of Mg0.60 not being higher than that of Mg0.45.…”
Section: Solute Balancementioning
confidence: 90%
“…The addition of Mg mainly affects the formation of Mg 2 Si and the distribution of solute elements in the matrix. Ni Tian et al [12] found that the volume of Mg 2 Si was gradually increased, while the divorced eutectic phenomenon of the quaternary eutectic structure was weakened with the increase in Mg content. After T6 treatment, the fine dispersed β(Mg 2 Si) phase and the Q(Al 5 Cu 2 Mg 8 Si 6 ) phase precipitated successively, which played a dispersion strengthening role in the alloy.…”
Section: Introductionmentioning
confidence: 99%